EFFECT OF BETA ADRENERGIC ANTAGONIST ON THE PRODUCTION OF TESTOSTERONE BY RAT’S LEYDIG CELLS
Background: The Leydig cell is the source of the male sex steroids, or androgens, which are essential for the maintenance of the male phenotype, the male gonads, and spermatogenesis. It has been reported that patients taking beta-blockers experience sexual dysfunction. The purpose of this study was to explore the direct mechanism by which beta adrenergic antagonist exert its’ effect on testosterone production by rat Leydig cells. Methods: Enzymatic dispersion of rat Leydig cell was done. About 85000 cells per tube were taken. After removal of endogenous testosterone by pre-incubation, The rat Leydig cells were incubated with varying concentrations of Atenolol: [Selective Beta-Adrenergic Antagonist